Reactions of Organotin(IV) Compounds with Platinum Complexes. Part IV*: Mechanisms of Reactions between SnR3Cl Compounds and Pt(0) Complexes - A. K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
The reaction of SnR3Cl (R = alkyl) with platinum(0) complexes in dichloromethane is found to initiate via insertion of Pt(0) into Sn-R bonds forming complexes containing the Pt(R)(SnR2Cl) species. The mechanism of formation of Pt-R bonds is believed to proceed via two intermediates containing Pt(II) and Pt(IV) complexes, respectively. Several reactions between SnR3Cl and [Pt(C2H4)(PPh3)2] alone and between SnR3Cl and [Pt(C2H4)(PPh3)2] in the intermediates by using 31P-NMR spectroscopy. The 119Sn-NMR spectra of some of the so formed complexes and other related complexes have been recorded.